Shifts in the skin microbiome associated with diaper dermatitis and emollient treatment amongst infants and toddlers in China. Issue 11 (16th September 2019) - Zheng, Yumei; Wang, Qian; Ma, Laiji; Chen, Yuanyuan; Gao, Ying; Zhang, Gaolei; Cui, Shumei; Liang, Haiyun; Song, Liya; He, Congfen
Abstract: Background: The microbiological basis of diaper dermatitis has not been clearly elucidated; however, a better understanding of microbial colonization may be vital for developing appropriate therapies. Methods: Using 16S‐rRNA gene sequencing technology, we characterized and compared the bacterial communities obtained from the buttock skin sites of children with diaper dermatitis and from healthy controls. Bacterial diversity in the buttock lesion area and subsequent recovery after emollient treatment have been discussed herein. Results: In buttock skin of children with or without diaper dermatitis, Staphylococcus and Anaerococcus were predominant in the total skin microbiome. Compared with the healthy group, the overall skin bacterial richness and diversity were higher in children with diaper dermatitis, with the abundance of Proteobacteria being significantly higher. In the diaper dermatitis group, the richness of Enterococcus, Erwinia and Pseudomonas was significantly higher, and the levels of Clostridium and Actinomyces were significantly lower than those in healthy children . Richness of Staphylococcus aureus was significantly higher in the diaper dermatitis group, whereas that of Staphylococcus epidermidis and Bifidobacterium longum was lower. Staphylococcus epidermidis and Staphylococcus haemolyticus, the dominant species found in buttock skin, were observed to recover earlier after the disease had improved through emollient treatment. Conclusion: Staphylococcus epidermidis, as skin probiotic bacterium, and B longum, Clostridium butyricum and Lactobacillus ruminis, which are intestinal probiotic bacteria, are significantly decreased in diaper dermatitis lesions. These changes in the buttock skin microflora indicate an imbalance in the microflora and suggest that the intestinal microflora may be undergoing dynamic changes. The results of this study suggest that probiotic bacterial supplementation may be useful in the treatment and prevention of diaper dermatitis.